Soil fertility in mixed crop-livestock farming systems of Punjab, Pakistan: The role of institutional factors and sustainable land management practices - Sheikh, Asjad Tariq; Chaudhary, Ashok Kumar; Mufti, Samaa; Davies, Stephen; Rola-Rubzen, Maria Fay (Elsevier, 2024)
CONTEXT Soil salinization is a significant environmental challenge prevalent in arid and semi-arid regions, causing adverse effects on crop yields and jeopardizing household food security. Previous research has examined the influence of institutional dynamics and the adoption of sustainable land management practices in bolstering agricultural output, and some have investigated the interplay among socioeconomic determinants, institutional frameworks, and the uptake of climate-resilient and sustainable methodologies, or the association between soil health and agricultural productivity. Yet, there has been a lack of studies that considered this relationship altogether and their role in enhancing soil fertility.